2002
DOI: 10.1142/s0129183102003413
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Model for Stocks Markets

Abstract: A new model for stocks markets using integer values for each stock price is presented. In contrast with previously reported models, the variables used in the model are not of binary type, but of more general integer type. It is shown how the behavior of the noisy and fundamentalists traders can be taken into account simultaneously in the time evolution of each stock price. The simulated time series is analysed in different ways order to compare parameters with those of real markets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In physics to understand financial market dynamics a variety of agent-based models have been proposed and examined [19,20,21,22,23,24,25,27,28,29,30,31,32,33]. It is found that to some extent those models are able to capture some of stylized facts such as fat-tailed distributions of returns and long autocorrelation times of the absolute returns.…”
Section: Introductionmentioning
confidence: 99%
“…In physics to understand financial market dynamics a variety of agent-based models have been proposed and examined [19,20,21,22,23,24,25,27,28,29,30,31,32,33]. It is found that to some extent those models are able to capture some of stylized facts such as fat-tailed distributions of returns and long autocorrelation times of the absolute returns.…”
Section: Introductionmentioning
confidence: 99%
“…From a theoretical point of view, it is clear that it could be very useful to have available a model that could reproduce as closely as possible the behavior of real-world markets. Here a multiscaling analysis on the time series generated by a recently reported model for stock markets is presented [6]. It is found that the scaling properties of the artificial time series generated by the model are in excellent agreement with those of actual time series.…”
Section: Introductionmentioning
confidence: 92%
“…On the other hand, several computational models trying to represent the behavior of actual stock markets have been presented [6,7,8,9]. From a theoretical point of view, it is clear that it could be very useful to have available a model that could reproduce as closely as possible the behavior of real-world markets.…”
Section: Introductionmentioning
confidence: 99%
“…Actually many models are able to capture some of the stylized facts. [3][4][5][6][7][8][9][10][11][12][13][14] In empirical finance the volatility is an important value to measure the risk. One of the stylized facts of the volatility is that the volatility of price returns changes in time and shows clustering, so called "volatility clustering".…”
Section: Introductionmentioning
confidence: 99%